Pengaruh Kejelasan Sasaran Anggaran Dan Pengendalian Internal Terhadap Akuntabilitas Kinerja Instansi Pemerintah (Studi Di Organisasi Perangkat Daerah Kabupaten Gorontalo) - Regita Padmadiani; Harun Blongkod; Ayu Rakhma Wuryandini (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aimed to determine the influence of budget goals clarity and intrnal control on the performance accountability of government agencies in the Gorontalo Regency regional Apparatus Organizations. Government officials in the Gorontalo Regency Regional Apparatus Organization made up the population of this study, whereas a total of 123 respondents were drawn from that group based on the sample criteria, which included heads of services, secretaries, treasurers, finance sectors, budget sectors, planning sectors, asset sectors and technical implementation officers (PPTK). The test was conducted and analyzed descriptively, employing structural equation modelling with the aid of the AMOS 24 and SPSS 25 program. The findings prove that (1) budget goals clarity had no positive and significant influence on the performance accountability of government agencies in the Gorontalo Regency regional Apparatus Organizations; (2) internal control had a positive and significant influence on the performance accountability of government agencies in the Gorontalo Regency regional Apparatus Organizations; (3) budget goals clarity and internal control simultaneously had a positive and significant influence on the performance accountability of government agencies. Keywords: Budget Goals Clarity; Internal Control; Performance Accountability of Government Agencies